Long-term antibody persistence after a booster dose of quadrivalent meningococcal ACWY-tetanus toxoid conjugate vaccine in healthy 5-year-old children. Issue 22 (8th May 2020) - Vesikari, Timo; Forsten, Aino; Laudat, France; Li, Ping; Van Der Wielen, Marie; Hezareh, Marjan; Perez, John L.; Webber, Chris
Highlights: MenACWY-TT booster 4 y postvaccination in toddlers may afford long-term IMD protection. Long-term MenACWY-TT antibody persistence against groups ACWY was shown 6 years postbooster. No lack of efficacy or vaccine-related AEs were reported 6 y postbooster. Abstract: Background: To provide continuing protection, available meningococcal vaccines must provide long-term persistence of circulating functional antibodies against prevalent serogroups causing invasive meningococcal disease (IMD). This study assessed antibody persistence and safety of the quadrivalent meningococcal vaccine conjugated to tetanus toxoid (MenACWY-TT) and the meningococcal serogroup C vaccine conjugated to Corynebacterium diphtheriae CRM197 protein (MenC-CRM) for up to 6 years after booster dosing in children. Methods: In the primary vaccination study, children were vaccinated at age 12 to 23 months. In the first extension study, children who completed the primary study received a booster dose 4 years later with the same primary vaccine. The current study assessed antibody persistence at 2 to 6 years postbooster against each of the 4 meningococcal serogroups using serum bactericidal assays using rabbit (rSBA) or human (hSBA) complement with antibody titer thresholds of ≥1:8 or ≥1:4, respectively, and geometric mean titers (GMTs). Safety evaluations during this period included serious adverse events (SAEs) related to vaccination and any event related to lack of vaccine efficacy. Results: A total of 184 subjects were enrolled (MenACWY-TT = 159; MenC-CRM = 25). For MenACWY-TT, the percentages of subjects with rSBA titers ≥1:8 ranged from 96.7% to 100% across serogroups at 2 years postbooster and 71.6% to 94.0% at 6 years postbooster; rSBA GMTs decreased from Year 2 to 4 and generally remained stable thereafter. The percentages of subjects in the MenACWY-TT group with hSBA titers ≥1:4 were 70.0% to 100% across serogroups at 2 years postbooster and 58.5% to 98.5% at 6 years postbooster. No lack of efficacy, SAEs, or vaccine-related adverse events were reported. Conclusions: The persistence of rSBA and hSBA antibodies was shown up to 6 years postbooster (10 years postprimary vaccination) with either MenACWY-TT or MenC-CRM, suggesting that this schedule may provide long-term protection against IMD. Clinicaltrials.gov: NCT01900899.